1981
DOI: 10.1037/0021-843x.90.4.286
|View full text |Cite
|
Sign up to set email alerts
|

Schematic processing and self-reference in clinical depression.

Abstract: Differences in self-schema content among 16 clinical depressives, 16 nondepressed psychiatric control patients, and 16 normal nondepressives (women between the ages of 18 and 65) were investigated by having subjects make structural (Small letters?), semantic (Means same as a given word?), and self-referent (Describes you?) ratings on depressed-and nondepressed-content personal adjectives. These ratings were then followed immediately by an incidental recall period in which subjects recalled as many of the adjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

29
414
4
7

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 434 publications
(467 citation statements)
references
References 15 publications
29
414
4
7
Order By: Relevance
“…Indeed, the self-system of depressed individuals has been described as a highly interconnected network of negative content (Beck, 1967;Beck et al, 1979), and negative self-referential effects have been demonstrated in a large number of cognitive tasks. For example, in adjective rating tasks, depressed participants have been found to endorse more negative and fewer positive adjectives as self-descriptive than do nonpsychiatric control participants (e.g., Derry & Kuiper, 1981). It stands to reason that if idiographic stimuli differentially activate depressed persons' negative selfschemas, these stimuli should produce a more severe dysphoric state in depressed persons (i.e., more reported sadness and less reported happiness) than would normative comparison stimuli.…”
Section: Type Effects: the Significance Of Idiographic Stimulimentioning
confidence: 99%
“…Indeed, the self-system of depressed individuals has been described as a highly interconnected network of negative content (Beck, 1967;Beck et al, 1979), and negative self-referential effects have been demonstrated in a large number of cognitive tasks. For example, in adjective rating tasks, depressed participants have been found to endorse more negative and fewer positive adjectives as self-descriptive than do nonpsychiatric control participants (e.g., Derry & Kuiper, 1981). It stands to reason that if idiographic stimuli differentially activate depressed persons' negative selfschemas, these stimuli should produce a more severe dysphoric state in depressed persons (i.e., more reported sadness and less reported happiness) than would normative comparison stimuli.…”
Section: Type Effects: the Significance Of Idiographic Stimulimentioning
confidence: 99%
“…Recent research has shown that systematic distortions of the self-concept may restrict the benefits to be derived from self-comparisons to only certain material consistent with the distortion or may possibly eliminate such benefits altogether. For example, Davis and Unruh (1981) and Derry and Kuiper (1981) have examined self-referencing in depressed subjects and have found that depressives either show no benefits from self-comparisons, allegedly due to an unstable self-concept, or show processing benefits only for material consistent with a depressed self-image, presumably indicating a stable self-concept organized around a nonnormal focus. In terms of a content limitation, it might be that elderly subjects would benefit only from material related specifically to the aging component of the self-concept (e.g., retirement, illness, loneliness, isolation, etc.)…”
mentioning
confidence: 99%
“…En ocasiones, la selección se ha basado simplemente en el juicio de expertos (p.ej., Mogg y Mathevi's, 1990; Medina, 1997), de los propios experimentadores (p.ej., Foa, McNally y Murdock, 1989) o en el juicio que los propios sujetos emiten en algún momento del proceso sobre el significado connotativo o denotativo de las palabras (p.ej., Derry y Kuiper, 1981;Ingram, Lumry, Cruet, y Sieber, 1987; Blanch y Baños, 1996). En otras ocasiones, las palabras utilizadas se han extraído directamente de instrumentos de personalidad, inventarios de sínto-mas, o cualquier instrumento de evaluación que emplee términos relacionados con el constructo bajo estudio.…”
Section: Self-referent Depressive Adjectives An Neutral-content Adjecunclassified